A systematic strategy for harnessing financial information systems in fighting corruption electronically - Ameen, Ali Abdulbaqi; Ahmad, Kamsuriah (2014)
Knowledge Management (KM) is one of the hottest topics in both of the industrialized world and information research world. In our daily life, we deal with the most related systems, which were Financial Information Systems (FIS).These systems have closely linked with all aspects of administrative organizations.As a result of this link, the KM has contributed in developing FIS as attempts to harness it as part of anti-corruption strategies.This research aims to propose a systematic strategy for harnessing FIS in fighting corruption electronically.This proposed strategy demonstrates a general perceptive during the designing and implementing phases.The research has employed a repetitive design methodology, which comprises an extensive literature review, content and website analysis.Initially, the approach explores the key concepts of FIS, corruption strategies, and the popular approaches employed to minimize corruption.Cumulatively the systematic strategy has been proposed for enabling the FIS to minimize corruption.This research suggests that the FIS should be employed heavily in the process of minimizing corruption.